Análise econômica da alface americana em monocultura e consorciada com pepino japonês em ambiente protegido - Barros Junior, Aurelio Paes [UNESP]; Alves Rezende, Braulio Luciano [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP]; de Queiros Porto, Diego Resende [UNESP]; da Silva, Gilson Silverio [UNESP]; Espagnoli Geraldo Martins, Maria Inez [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
The experiment was carried in green house at Unesp, Jaboticabal-SP, in the period of August and November, with objective to evaluate the production cost and crisphead lettuce "Lucy Brown" profitability in monoculture and in intercropping with Japanese cucumber "Hokushin" in protected environment. The production cost determination was performed on total operational cost (COT) basis. The crisphead lettuce in monoculture estimated COT and in intercropping was R$ 657,57 and R$ 159,95/614,4 m(2) respectively. The productivities of 623 and 730 kg/614,4 m(2) in the experiments had provided gross incomes of 286,58 R$ and 335,80/614,4 m(2). It was verified a loss of R$ 370,99/614,4 m(2) in the crisphead lettuce monoculture and an operational profit of R$ 175,85/614,4 m(2), in protected environment when in intercropping with cucumber.

O experimento foi conduzido em casa de vegetação, na Unesp, Jaboticabal-SP, no período de agosto e novembro, com objetivo de avaliar o custo de produção e a rentabilidade da alface americana ‘Lucy Brown’ em monocultura e consorciada com pepino japonês ‘Hokushin’ em ambiente protegido. A determinação do custo de produção foi realizada com base no custo operacional total (COT). O COT estimado da alface americana em monocultura e consórcio foi de R$ 657,57 e R$ 159,95/614,4 m2, respectivamente. As produtividades de 623 e 730 kg/614,4 m² em monocultura e em consórcio, respectivamente, proporcionaram receitas brutas de R$ 286,58 e R$ 335,80/614,4 m2. Verificou-se um prejuízo de R$ 370,99/614,4 m2 na monocultura de alface americana e lucro operacional de R$ 175,85/614,4 m², quando consorciado com o pepineiro em ambiente protegido
Economic analysis of crisphead lettuce in monoculture and intercropping with japanese cucumber in protected environment
Keywords: Cucumis sativus L. Lactuca sativa; Production cost; Economic viability